2010
DOI: 10.1002/art.27478
|View full text |Cite
|
Sign up to set email alerts
|

Statins, inhibitors of 3‐hydroxy‐3‐methylglutaryl‐coenzyme A reductase, function as inhibitors of cellular and molecular components involved in type I interferon production

Abstract: Objective. Statins, which are used as cholesterollowering agents, have pleiotropic immunomodulatory properties. Although beneficial effects of statins have been reported in autoimmune diseases, the mechanisms of these immunomodulatory effects are still poorly understood. Type I interferons (IFNs) and plasmacytoid dendritic cells (PDCs) represent key molecular and cellular pathogenic components in autoimmune diseases such as systemic lupus erythematosus (SLE). Therefore, PDCs may be a specific target of statins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 50 publications
(93 reference statements)
3
34
0
Order By: Relevance
“…This has been demonstrated with blood-derived PDC obtained from healthy donors, as well as from patients with SLE 97 . Statin treatment also inhibits TNF secretion by human PDC in response to either TLR7 (loxoribine) or TLR9 (CpGA) ligands 97 . These data have been confirmed in vivo using ssRNA Sendai virus 97 .…”
Section: The Influence Of the Metabolism On Innate Immune Functionmentioning
confidence: 79%
See 2 more Smart Citations
“…This has been demonstrated with blood-derived PDC obtained from healthy donors, as well as from patients with SLE 97 . Statin treatment also inhibits TNF secretion by human PDC in response to either TLR7 (loxoribine) or TLR9 (CpGA) ligands 97 . These data have been confirmed in vivo using ssRNA Sendai virus 97 .…”
Section: The Influence Of the Metabolism On Innate Immune Functionmentioning
confidence: 79%
“…Inhibition of the mevalonate pathway ( i.e ., de novo cholesterol biosynthesis) by statins (simvastatin and pitavastatin) blocks TLR7- and TLR9-induced type I IFN production by human PDC ( Figure 3) 97 . This has been demonstrated with blood-derived PDC obtained from healthy donors, as well as from patients with SLE 97 .…”
Section: The Influence Of the Metabolism On Innate Immune Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amuro et al [46] isolated human plasmacytoid dendritic cells, essential to the development of systemic lupus erythematosus and found that treatment with statins inhibited the production of pro-inXammatory cytokines interferon-alpha and tumor necrosis factor-alpha. In addition to chemokine downregulation [47], statins also positively modify cholesterol lipid rafts in T cells, resulting in inhibition of cellular activation and production of interleukins [48].…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
“…For example, patients with sickle cell disease can develop oxidative stress and chronic inflammation to their distal vasculature as a result of transient vaso-occlusion and subsequent [196][197][198] Decrease decline in GFR Prevent contrast induced acute kidney injury Decrease risk of stroke Fracture injuries, bone healing, & osteoporosis [199][200][201][202][203][204] Promote mesenchymal cell differentiation to osteoblasts Protect osteoblasts from apoptosis Reduce osteoclast activity and bone resorption HIV [205][206][207][208][209][210][211] Slow progression of vascular disease on ART Improve flow-mediated vasodilation Implement immunomodulation Reduce all-cause mortality Immunomodulation [212][213][214] Inhibit interferon production Decrease T cell activation Infection [215][216][217][218] Reduce risk of mortality from bacterial and viral infection Lupus [219][220][221][222] Reduce C-reactive protein Reduce circulating chemokines Improve endothelial function Polycystic ovary syndrome [223][224][225] Reduce markers of inflammation Reduce androgenic steroid concentrations Rheumatoid arthritis [226][227][228][229][230][231] Reduce risk of mortality Reduce joint pain/swelling Reduce markers of inflammation Rotator cuff injury 232,233 Stimulate migration and adhesi...…”
Section: Future Considerationsmentioning
confidence: 99%